Nasoenteral tube: factors associated with delay between indication and use in emergency services - Franciele Anziliero; Ana Paula Almeida Corrêa; Bárbara Amaral da Silva; Bárbara Elis Dal Soler; Érica Batassini; Mariur Gomes Beghetto
ABSTRACT Objective: to know the time between indication and use of a nasoenteral tube (NET) and factors associated with delays. Method: A prospective cohort study that followed adults in a Brazilian emergency department, since the indication of the use of a NET, evaluating clinical variables and the work process. The Generalized Estimated Equations model was adopted to identify factors associated with the delays in each stage of the process. Results: the time between indication and use of NET was 573 (IQR: 3601,093) minutes, in 150 insertions of NET. Insertions in patients who previously did not use it; delays in the medical, nutrition, and nursing care routine; use of mechanical ventilation; noradrenaline; and fasting were factors for longer time before the use of the tube. Conclusion: the time between indication and use of NET was high, exceeding 10 hours in half of the cases. Factors related to the clinical condition of the patient and to the care management would contribute to delays.